Determination of critical control points on the chocolate bar production process in pt. cocoa chocolate, bandar lampung - Awangsih, Wida; Juwitaningtyas, Titisari (Universitas Ahmad Dahlan, 2021)
PT. Aneka Coklat Kakoa is one of the food industries engaged in the food processing of chocolate products in Bandar Lampung. Chocolate products are processed food that is easily contaminated by microorganisms and processes their production is a risk to food safety, so it is necessary to handle it which is good to prevent this risk. That is the basis of the need for effort supervision of the chocolate bar processing process to minimize the possibility of the occurrence of danger. Hazard Analysis and Critical Control Point (HACCP) is a guaranteed system of food safety based on that hazards can occur at the point or stage of production certain, but the danger can be controlled. Its control measures for ensuring food safety are based on existing principles for identifying possible dangers at any stage of the food chain. One of the steps in applying HACCP is the determination of critical control points (CCP) by a method used in determining this critical control point: a decision tree diagram. Based on the results of the study, it was obtained that the critical control point is in the process of roasting, grinding, ball milling, packaging, and storage.